Anti-RAGE (Receptor Advanced Glycation End products) Antibody Improves Diabetic Retinopathy in Rats via Hypoglycemic and Anti-inflammatory Mechanism - Indiarsih, Tiara Bunga; Amin, Ramzi; Ansyori, A.K. (Majalah Oftalmologi Indonesia, 2023)
Background: Receptor advanced glycation end products (RAGE) activation plays an essential role in diabetic retinopathy (DR) progression. This study was aimed to explore the role of anti-RAGE antibodies (RAGE antagonists) in inhibiting DR progression through their hypoglycemic and anti- inflammatory mechanism in diabetic retinopathy induced rats. Methods: A total of 30 male Wistar rats were randomly divided into five group. The group was consisted of normal control group, DR group without treatment, DR group with anti-RAGE 1 g/kg BW, 10 g/kg BW, and 100 g/kg BW. To assess the diabetic retinopathy, fundus photographs were taken every week using a camera with 16x magnification placed in front of the rat's eyes. Blood glucose was checked by the glucose oxidase-peroxidase method. Retinal TNF-? levels and VEGF were examined using an enzyme-linked immunosorbent assay (ELISA) kit. Results: The finding of this study showed that anti-RAGE treatment at dose of 10 and 100 g/kg BW, HbA1c levels were significantly higher (p< 0.05) compared to the normal control group but significantly lower (p< 0.05) than in the diabetes group. The mean blood vessel diameter in the DR+anti-RAGE 10 and 100 g/kg BW groups was significantly lower than in the diabetic retinopathy group (p< 0.05). The administration of anti-RAGE 10 and 100 g/kg BW showed the ability to significantly reduce VEGF levels compared to the DR group (p< 0.05). Conclusions: This study revealed at doses of 10 and 100 g/kg BW, anti-RAGE antibodies improved diabetic retinopathy in Wistar rats through hypoglycemic effects and anti-inflammatory mechanisms.